2020
DOI: 10.5858/arpa.2019-0569-oa
|View full text |Cite
|
Sign up to set email alerts
|

Digital Whole Slide Imaging Compared With Light Microscopy for Primary Diagnosis in Surgical Pathology

Abstract: Context.— The adoption of digital capture of pathology slides as whole slide images (WSI) for educational and research applications has proven utility. Objective.— To compare pathologists' primary diagnoses derived from WSI versus the standard microscope. Because WSIs differ in format and method of observation compared with the current standard glass slide microscopy, this study is critical to potential clinical adoption of digital pathology. Design.— The study enrolled a total of 2045 cases enriched for more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 21 publications
(29 reference statements)
1
101
0
Order By: Relevance
“…A Q-probe study performed by the College of American Pathologists analyzed self-reported laboratory discrepancy frequencies by prospective secondary review of glass slides to be a median of 5.1%, for anatomic pathology [33]. In addition, as previously published and accepted by the Food and Drug Administration in two other studies, the major discordance rate compared to a reference diagnosis was 4.9% for whole slide images and 4.6% using glass slides in one study [2]; and 3.6% for whole slide images and 3.2% for glass slides in another study [1]. In our study, the reference standard was designated as conventional light microscopy.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A Q-probe study performed by the College of American Pathologists analyzed self-reported laboratory discrepancy frequencies by prospective secondary review of glass slides to be a median of 5.1%, for anatomic pathology [33]. In addition, as previously published and accepted by the Food and Drug Administration in two other studies, the major discordance rate compared to a reference diagnosis was 4.9% for whole slide images and 4.6% using glass slides in one study [2]; and 3.6% for whole slide images and 3.2% for glass slides in another study [1]. In our study, the reference standard was designated as conventional light microscopy.…”
Section: Discussionmentioning
confidence: 75%
“…At MSK, whole slide scanners from multiple vendors and custom viewer software haven been implemented and validated to support clinical workflow. The aims of this study include: (1) to assess operational feasibility supporting remote review and primary reporting of pathology specimens using digital pathology systems; (2) to evaluate remote access performance and usability for pathologist remote signout; (3) to validate a digital pathology system for remote primary diagnostic use.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies have consistently reported high, intermediate, and low discordant rates for bladder, breast, and gastrointestinal tract specimens, respectively [41,42]-a finding suggesting intrinsic difficulties of specific areas. In contrast, we observed 4%, 8%, and 12% of discrepancies for urology, gastrointestinal tract, and breast specimens.…”
Section: Principal Findingsmentioning
confidence: 94%
“…A more recent review, covering studies published until 2018, reported a disagreement ranging from 1.7% to 13% [10]. Two multicentric, randomized, non-inferiority studies reported major discordant rates of 4.9% [41] and 3.6% [42] between diagnoses done by digital and glass slides. Furthermore, a study from a single, large academic center reported an overall diagnostic equivalency of 99.3% [43].…”
Section: Principal Findingsmentioning
confidence: 99%
“…32 Several published studies have reported low major and minor discrepancy rates, demonstrating that diagnoses rendered by WSI are not inferior to primary diagnoses via traditional histopathology. [33][34][35][36][37][38][39][40][41][42][43][44][45] Per the College of American Pathologists (CAP; GEN.52920), each laboratory must validate WSS/WSI platforms for each clinical diagnostic usage by performing its own validation study. 46 Owing to the COVID-19 pandemic, CAP initiated advocacy efforts geared toward a temporary waiver of current regulations limiting remote review of pathology slides in sites physically outside of the Clinical Laboratory Improvement Amendments (CLIA)-accredited laboratory as set by the Centers for Medicare & Medicaid Services (CMS) and the Department of Health and Human Services.…”
mentioning
confidence: 99%